The COVID-19 pandemic impact on away and home victories in soccer and rugby union - Sedeaud, A.; de Larochelambert, Q.; Schipman, J.; Toussaint, J.-F. (Frontiers in Sports and Active Living, 2021)
Objective: To measure the impact of restrictions due to COVID on the proportion of matches won at home, away and draw in professional soccer and rugby union.